FRF MODELING OF KANTILEVER BEAM USING NASTRAN FEMAP V9.3 - ADIGUNA (NIM : 13106136); Pembimbing : Dr. Ir. Zainal Abidin, YONATHAN
Dynamic characteristics of the machine structure can be represented by FRF (Frequency Response Function). FRF is needed to predict the response when the input force is known. This thesis aims to conduct FRF from modeling with finite element method using Nastran Femap v9.3 software. In this study, modeling is limited in the frequency range of 100 Hz or first three dominant mode shape. In addition to modeling, FRF was also obtained from the test results. Two methods of FRF testing is done by the impact hammer and the vibration exciter. There is a small difference between the natural frequencies obtained from this two tests. Differ from the natural frequency, damping ratios obtained from this two tests show a huge difference. FRF modeling begins by comparing the natural frequency results from modeling and testing. The FRF modeling can be done after the natural frequency between the results of modeling, theoretical calculations and testing get small differences. Unlike the natural frequency, there is still a big difference for the FRF magnitude between the modeling and FRF testing using impact hammer. The difference is due to calculation error of damping ratio. Nonetheless, the FRF magnitude from the modeling and FRF testing using vibration exciter has been successfully matched for the first three mode shape.